Potential of biological control agents against Tuta absoluta (Lepidoptera: Gelechiidae): current knowledge in Argentina - Luna, María Gabriela (2015)
Pest suppression through biological control seeks to maximize the action of the pest's natural enemies with the goal of reducing pesticide use. We present a summary of published studies and original findings on several entomophagous species as biocontrol agents of Tuta absoluta (Meyrick, 1917) (Lepidoptera: Gelechiidae), a key pest of tomato crops in Argentina, with the aim to select potential candidates for its management. Spontaneously occurring T. absoluta egg parasitism was lower than that inflicted by the larval parasitoids Dineulophus phthorimaeae (De Santis, 1983) (Hymenoptera: Eulophidae) and Pseudapanteles dignus (Muesebeck, 1938) (Hymenoptera: Braconidae). These parasitoids exhibit important life history traits in laboratory conditions and produce relevant amounts of T. absoluta mortality in the field. Surveys carried out in Tucumán and Buenos Aires provinces, Argentina, revealed that D. phthorimaeae and P. dignus coexist in tomato and eggplant crops; T. absoluta-P. dignus interaction is also found on other non-cultivated solanaceous species present in horticultural farms. In addition, studies are currently under way to determine the predation ability of Zelus obscuridorsis (Stål, 1860) (Hemiptera: Reduviidae) on both larvae and adults of the pest. Finally, we discuss the prospects for implementing experimental augmentative releases of P. dignus to control the pest, a candidate selected considering various positive biological traits and because of its simple mass production and manipulation compared with other antagonists of T. absoluta.